124k views
5 votes
Which function rule produces the following graph?

A. Y - 1 = -2/3 ( x + 3)
B. Y + 1 = -2/3 (x + 3)
C. Y - 1 = -2/3 (x - 3)
D.Y + 1 = -2/3 (x - 3)

Which function rule produces the following graph? A. Y - 1 = -2/3 ( x + 3) B. Y + 1 = -2/3 (x-example-1
User Elisabete
by
5.3k points

2 Answers

0 votes

The answer you want is going to be A

Im the other one

It is still me nhampton9675

User Maria Ivanova
by
5.1k points
6 votes

The answer you want is going to be A

Hope it helps!!


User Marek Lisiecki
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.